The impact of verbal and nonverbal auditory resources on explicit foreign language vocabulary learning. (October 2019) - Kaplan-Rakowski, Regina; Loranc-Paszylk, Barbara
Abstract: Auditory resources can make language learning more effective. This quantitative study examined the impact of verbal and nonverbal auditory resources via a multimedia presentation on explicit foreign language (FL) vocabulary learning. We compared the effectiveness of four learning conditions, in which 216 Polish speakers were exposed to new English words provided with verbal or nonverbal auditory resources: (1) pronunciation, (2) sound effects, (3) pronunciation plus sound effects, or (4) no audio (control condition). A one-way repeated analysis of variance revealed that vocabulary with nonverbal auditory resources (i.e., sound effects) was associated with significantly higher scores compared with vocabulary with no audio. Vocabulary with verbal auditory resources (i.e., pronunciation) alone or with the combination of verbal and nonverbal auditory resources (i.e., pronunciation plus sound effects) showed no significant differences from the condition with no audio. Both immediate and seven-day delayed posttests confirmed the positive learning impact of sound effects. This study has practical implications for teachers or instructional designers, suggesting that they should consider including relevant sound effects when introducing vocabulary to language learners. Highlights: Vocabulary presented with sound effects is associated with significantly higher scores compared with vocabulary with no audio. Vocabulary presented with pronunciation shows no significant differences from the condition with no audio. Vocabulary presented with the combination of pronunciation and sound effects shows no significant differences from the condition with no audio.